Development of Interactive Learning Media Using Articulate Storyline 3 to Facilitate Students' Mathematical Problem-Solving Skills in Statistics SMA/MA - Hastri, Sherly; Heleni, Susda; Hutapea, Nahor Murani (Journal of Educational Sciences, 2025)
This research aims to develop an interactive learning media using Articulate Storyline 3 to facilitate students’ mathematical problem-solving skills in statistics at the high school level. The development process utilized the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The media was designed to guide students through the steps of problem-solving, including understanding the problem, planning the solution, executing the plan, and evaluating the solution.   The developed media was validated by experts and found to be highly valid. A small-scale and large-scale trial was conducted to assess the media's effectiveness. Results from the small-scale trial showed that the media was highly practical for students with varying abilities. The large-scale trial also indicated that the media was practical and effective in facilitating students' mathematical problem-solving skills.   In conclusion, the developed interactive learning media is a valuable tool to enhance students' mathematical problem-solving skills in statistics. It provides a structured and engaging learning experience is proven to be valid and practical that can help students develop critical thinking and problem-solving abilities.